Dose and time-dependence of acute intermittent theta-burst stimulation on hippocampus-dependent memory in parkinsonian rats - Wang, Yixuan; Liu, Jian; Hui, Yanping; Wu, Zhongheng; Wang, Ling; Wu, Xiang; Bai, Yihua; Zhang, Qiaojun; Li, Libo (Frontiers in Neuroscience, 2023)
Background: The treatment options for cognitive impairments in Parkinson’s disease (PD) are limited. Repetitive transcranial magnetic stimulation has been applied in various neurological diseases. However, the effect of intermittent theta-burst stimulation (iTBS) as a more developed rTMS paradigm on cognitive dysfunction in PD remains largely unclear. Objective: Our aim was to explore the effect of acute iTBS on hippocampus-dependent memory in PD and the mechanism underlying it. Methods: Different blocks of iTBS protocols were applied to unilateral 6-hydroxidopamine-induced parkinsonian rats followed by the behavioral, electrophysiological and immunohistochemical analyses. The object-place recognition and hole-board test were used to assess hippocampus-dependent memory. Results: Sham-iTBS and 1 block-iTBS (300 stimuli) didn’t alter hippocampus-dependent memory, hippocampal theta rhythm and the density of c-Fos- and parvalbumin-positive neurons in the hippocampus and medial septum. 3 block-iTBS (900 stimuli) alleviated 6-hydroxidopamine-induced memory impairments, and increased the density of hippocampal c-Fos-positive neurons at 80 min post-stimulation but not 30 min compared to sham-iTBS. Interestingly, 3 block-iTBS first decreased and then increased normalized theta power during a period of 2 h following stimulation. Moreover, 3 block-iTBS decreased the density of parvalbumin-positive neurons in the medial septum at 30 min post-stimulation compared to sham-iTBS. Conclusion: The results indicate that multiple blocks of iTBS elicit dose and time-dependent effects on hippocampus-dependent memory in PD, which may be attributed to changes in c-Fos expression and the power of theta rhythm in the hippocampus.